2022
DOI: 10.3390/agronomy12010147
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Biochemical Traits Associated with Field Resistance of Onion Cultivars to Onion Thrips and the Effect of Mechanical Injury on the Level of Biochemical Compounds in Onion Leaves

Abstract: Thrips tabaci Lind. is a global pest and also represents a serious threat to onion production in Poland. In 2 years (2015–2016) of field studies, 8 onion cultivars were evaluated to characterize the resistance to onion thrips and to determine if any biochemical and anatomical features of onion plants are associated with antixenotic and/or antibiotic mechanisms of resistance. Additionally, the influence of mechanical injury on the content of several biochemical compounds in onion leaves was made. The resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 75 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…Aside from carbohydrates, thrips feeding preference could also be affected by the content of anthocyanins or other physiological factors based on the age of the plant. In onion, a significant positive correlation was described between the abundance of onion thrips ( Thrips tabaci Lind) and concentrations of total soluble sugars, reducing sugars, and sucrose, while a negative relationship was detected between the total phenolic content and thrips damage ( Pobożniak et al., 2022 ). When greenhouse thrips ( Heliothrips haemorrhoidalis Bouche) were compared for feeding preferences among several tree species, the levels of soluble proteins present had a greater influence on the susceptibility of the plants than the levels of carbohydrates ( Scott Brown et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from carbohydrates, thrips feeding preference could also be affected by the content of anthocyanins or other physiological factors based on the age of the plant. In onion, a significant positive correlation was described between the abundance of onion thrips ( Thrips tabaci Lind) and concentrations of total soluble sugars, reducing sugars, and sucrose, while a negative relationship was detected between the total phenolic content and thrips damage ( Pobożniak et al., 2022 ). When greenhouse thrips ( Heliothrips haemorrhoidalis Bouche) were compared for feeding preferences among several tree species, the levels of soluble proteins present had a greater influence on the susceptibility of the plants than the levels of carbohydrates ( Scott Brown et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, light-green accessions that are more resistant to INSV than dark-green accessions have a lower content of chlorophyll. Because chlorophyll is directly involved in the production of carbohydrates, light-green accessions commonly contain less glucose, fructose, and sucrose ( Simko et al., 2014 ), the compounds that may affect thrips feeding preference ( Scott Brown et al., 2002 ; Pobożniak et al., 2022 ). Aside from carbohydrates, thrips feeding preference could also be affected by the content of anthocyanins or other physiological factors based on the age of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Post-alighting host acceptance and subsequent feeding and reproduction are strongly influenced by the plant's nutritional quality and defenses such as secondary metabolites [43,44]. A negative relationship between the total phenol content and thrips damage was observed by researchers studying the biochemical basis of onions' resistance to T. tabaci [19,20]. Njau et al [19] and Bhonde et al [45] found that the total sugar content in the leaves of onion genotypes was positively correlated with the number of onion thrips, while Pobo żniak et al [20] confirmed the positive correlation between reducing sugar quantity and thrips density.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, some plant characteristics that are responsible for the partial resistance of onions to T. tabaci have been identified. The differences in resistant and susceptible cultivars have been associated with leaf color [14], the amounts and types of epicuticular leaf wax [15,16], plant architecture and anatomy [17,18], and total phenol content [19,20]. Recently, it was also possible to select some onion genotypes that showed a lower number of thrips compared to susceptible ones [19,21], and these produced large bulb yields under thrips pressure [17,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation